Bibliometric Analysis of Mindfulness Articles in Management Literature - Tolay, Ebru; Bağbancı, Berat (International Journal of Contemporary Economics and Administrative Sciences, 2024)
The use of mindfulness in management literature has gained increasing interest in recent years. To better understand this area, we conducted a bibliometric analysis of 597 articles from the Web of Science database. Our research allowed us to identify the distribution of articles by year, and the most influential authors, journals, and countries. By analyzing frequently occurring keywords and thematic clusters, we gained insight into the most commonly used terms in this field. We also conducted a keyword analysis of articles published in countries with substantial Buddhist populations in Asia, comparing them to those in Anglo, Latin American, European, Middle Eastern, and African countries. Moreover, we explored the various theories that explain mindfulness as it relates to management and examined the impact of the COVID-19 pandemic on the increased interest in this subject. Based on our findings, we made predictions about this field and proposed potential areas for future research.